A Teacher’s Use of Humor in An Indonesian EFL Classroom: An Analysis of Humor Types, Implementation Strategies, And Teacher–Student Perceptions - Ni Putu Rizki Diah Apriani Wibawa; Luh Putu Artini; Ni Putu Era Marsakawati (Universitas Islam Negeri Palopo, 2026)
This study explores an English teacher's use of humor in the classroom, focusing on its language and content, and its influence on students’ enjoyment of learning, engagement, participation, and classroom interaction. Although numerous studies have examined the benefits of using humor in EFL classrooms, limited qualitative research has explored how humor is constructed, implemented, and perceived in Indonesian EFL contexts. This research employed a qualitative case study design. It was conducted at a senior high school in Denpasar, Bali. The data were collected through classroom observation and semi-structured interviews with one English teacher and several students. To obtain in-depth data, the observations were conducted across three meetings. The collected data were analyzed using thematic analysis, categorizing humor by content and function. Unlike the previous findings, this study provides an in-depth qualitative analysis of humor types, implementation, strategies, and both the teacher and the students’ perceptions in an EFL classroom. Furthermore, the findings revealed that the teacher frequently used three types of humor: course-related, course-unrelated, and self-disparaging, delivered in English and Indonesian. Course-related humor was often incorporated into teaching materials to simplify concepts and improve understanding, while course-unrelated humor serves as an icebreaker to create a relaxed classroom atmosphere. The teacher used humor through three main strategies: introducing the lesson with humor, embedding it in teaching materials, and employing spontaneous humor during classroom interactions. Furthermore, both students and the teacher perceived humor positively, reporting that humor can increase enjoyment, confidence, and willingness to engage in the classroom. However, the findings also highlight the importance of using humor appropriately, taking context, timing, and students’ characteristics into account to avoid negative impacts.